39-38w=39-38w

Simple and best practice solution for 39-38w=39-38w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-38w=39-38w equation:


Simplifying
39 + -38w = 39 + -38w

Add '-39' to each side of the equation.
39 + -39 + -38w = 39 + -39 + -38w

Combine like terms: 39 + -39 = 0
0 + -38w = 39 + -39 + -38w
-38w = 39 + -39 + -38w

Combine like terms: 39 + -39 = 0
-38w = 0 + -38w
-38w = -38w

Add '38w' to each side of the equation.
-38w + 38w = -38w + 38w

Combine like terms: -38w + 38w = 0
0 = -38w + 38w

Combine like terms: -38w + 38w = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 12x-18y=-36 | | 25w+8=8+25w | | 8+2[29-2(4-2)+3]= | | 9-4x=x+3 | | 7-21x=7-21x | | 9y-32=-16 | | 38+35w=35w-38 | | 9+[21-2(3-1)+3]= | | 4-(x-3)=-2x+9 | | -2(-t+3)-4t=-2t-7 | | 49x-86=49x+4 | | 41-47y=47y-55 | | -x-10=-7x+2 | | 25+38w=38w+25 | | Ax+Gy=J | | Cx+Hy=M | | 1*8= | | 21x-16=86+21x | | 35-26z=78-26z | | 7(3x+1)=(3x+1)7 | | 3x+6=9x-17 | | 3(t-2)+7t=5(2t+3)-8 | | 36=3(x+1) | | w-r=h | | 45x+22=22-45x | | ln(4x^2)+ln(e)-ln(3x)=1 | | 19-9x=4-6x | | 10-8x=4-5x | | 8+4(1-3t)=-3(t-4)+2 | | 3x(2x+15)=9x | | 6c-d=17+d | | 8z+10=11+11z |

Equations solver categories